The Wonder : a novel - Donoghue, Emma, 1969- (Little, Brown and Company, 2016)
"Tourists flock to the cabin of eleven-year-old Anna O'Donnell, who is said to be living without food, and a journalist is sent to cover the sensation. Lib Wright, a veteran of Florence Nightingale's Crimean campaign, is hired to keep watch over the girl. As Anna's life ebbs away, Lib finds herself responsible not just for the care of a child but for that child's very survival. Haunting and magnetic, The Wonder is a searing examination of doubt, faith, and what nourishes us, body and soul. Written with all the propulsive tension that made Donoghue's Room a huge bestseller, it works beautifully on many levels -- an intimate tale of two strangers who transform each other's lives, a powerful psychological thriller, and a spellbinding story of love pitted against evil." -- from back cover.